Achieving security by combining Huffman and SLSB algorithms - Alshaikhli, Imad Fakhri Taha; Alnasheet, Meshal M Y; Alahmad, Mohammad; Alashram, Sarah M. (Design for Scientific Renaissance, 2013)
Stenography is the art of hiding secret message into a cover media. Some of the usage for this algorithm is to protect the digital Holly Quran. This paper presents a novel stenographic algorithm based on the spatial domain. THE NEW ALGORITHM refers to a combined stenographic techniques; mainly Huffman algorithm and SLSB algorithm. The new method will both provide a less distortion images and increase the security. THE NEW ALGORITHM will use the hash digest from the Gear hash function as a secret message.